A New Educational Paradigm during the Pandemic. Human Development between Capability Approach and Digital - Fabiano, Alessio (Formazione & insegnamento, 2021)
The educational changes in our global society during the Pandemia, mediated by the digital, lead to a reflection on the possibility to construct a new educational paradigm. Concepts such as freedom, well-being, education and citizenship are deeply modified by a life that is always connected, in balance between virtuality and reality, between analog and digital. Rethinking these categories means elaborating new learning experiences in formal, non-formal and informal educational contexts. What kind of educational challenge does the twenty-first century teacher have to face? In this paper I will try to reflect on the importance of digital citizenship during Pandemia, the concept of the human development between the Capability Approach and digital, to define a cultural project for the teachers education in the contemporary Pandemia, fundamental in order to improve inclusive school and society.